(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Everyone makes mistakes, even speakers using their own language when they are hurried, ‘lost for words’, or forced into inappropriate language by a difficult or unusual situation. It is hardly surprising, then, that language learners make mistakes, given the difficulty of the task of comprehending, processing the content of the message and knowledge of the target language, and coming out with a response that is both grammatically correct and appropriate to the situation